Peranan Pancasila dalam Pengembangan Ilmu Pengetahuan di Era Gelobalisasi - Jakak, Pamuji Muhamad; Rifa'i, Muhamad Nanang; Azizah, Bella (Universitas Muhammadiyah Ponorogo, 2023)
The Role of Pancasila in the Development of Science In the Era of Globalization. English translation. The role of pancasila in the development of science in this era of globalization is important in the development of science, one of which is science. The main problem in this article is the lack of young people to update science such as not knowing knowledge about the use of learning media, for example the zoom meet application tool, even though when they master zoom meet it will make learning easier. The purpose of the research in this article is to explore the role of Pancasila in developing science at the student level. This research method uses the method of analyzing and reading journals, articles and books. The results and discussion in this article are to make it easier for us students to learn when the lecturer cannot attend. In practicing pancasila, it is very important to advance the country and graduate students who are based on pancasila. Research recommendations show that science in this era of globalization is very important and influential for students to form a developed and pancsila-based country that understands the values of pancasila and to realize an advanced learning atmosphere with no observance.